Survival Impact of Adjuvant Therapy in Salivary Gland Cancers following Resection and Neck Dissection. (June 2019) - Aro, Katri; Ho, Allen S.; Luu, Michael; Kim, Sungjin; Tighiouart, Mourad; Yoshida, Emi J.; Mallen-St Clair, Jon; Shiao, Stephen L.; Leivo, Ilmo; Zumsteg, Zachary S.
Objective: To evaluate the impact of postoperative radiotherapy (PORT) and chemotherapy on survival in salivary gland cancer (SGC) treated with curative-intent local resection and neck dissection. Study Design: Retrospective population-based cohort study. Setting: National Cancer Database. Subjects and Methods: Patients with SGC who were undergoing surgery were identified from the National Cancer Database between 2004 and 2013. Neck dissection removing a minimum of 10 lymph nodes was required. Because PORT violated the proportional hazards assumption, this variable was treated as a time-dependent covariate. Results: Overall, 4145 cases met inclusion criteria (median follow-up, 54 months). PORT was associated with improved overall survival in multivariable analysis, both ≤9 months from diagnosis (hazard ratio [HR], 0.26; 95% CI, 0.20-0.34; P < .001) and >9 months (HR, 0.75; 95% CI, 0.66-0.86; P < .001). In propensity score–matched cohorts, 5-year overall survival was 67.1% and 60.6% with PORT and observation, respectively ( P < .001). Similar results were observed in landmark analysis of patients surviving at least 6 months following diagnosis. Adjuvant chemotherapy was not associated with improved survival (HR, 1.15; 95% CI, 0.99-1.34; P = .06). Conclusion: PORT, but not chemotherapy, is associated with improved survival among patients with SGC for whom neck dissection was deemed necessary. These results are not applicable to low-risk SGCs not requiring neck dissection.